The Use of Ozone in the Pulmonary Obstructive Disease - Emma Borrelli (Disease and Health Research: New Insights Vol. 3, 2024)
It has been reported from recent scientific evidence that chronic obstructive pulmonary disease (COPD) is not only an inflammatory/oxidative lung alteration but also a multiorgan disease causing extrapulmonary manifestations like cardiovascular disease, neurological degenerations, musculoskeletal dysfunction and clinical depression. Experimental studies suggested that ozone therapy has unique properties in reducing inflammation and upregulating the cellular antioxidant system in chronic oxidative stress diseases. To evaluate the effects of ozone as integrated therapy in the treatment of COPD, we enrolled 80 patients affected by moderate/ severe COPD. 40 patients (Group A), in addition to standard therapy with inhaled bronchodilator and/or corticosteroids, underwent a cycle of oxygen ozonetherapy (major ozonated autohemotherapy, O3-AHT) twice a week for the first 5 weeks, thereafter a single treatment every week for other 10 weeks. The resting 40 patients (Group B) served as control and did not receive treatments otherwise the standard therapy with inhaled LABA / LAMA and/or corticosteroids. In Group A there was a significant increase in functional capacity assessed by 6 minutes walking test (415 ±101.1 m before the study vs 493.8 ± 105.2 m at the end of the study, p < 0.01) and a significant decrease in the degree of dyspnea measured by Borg scale and an improvement of the quality of life as reported in the results of Saint George Respiratory Questionnaire. The control group B showed no significant difference before and after the study. Even if the results of this study need to be confirmed with an ample clinical trial, the use of ozone seems to be an effective treatment for the improvement of the quality of life in COPD patients.